2021
DOI: 10.22158/wjeh.v3n2p15
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Working Mothers: A Phenomenological Study

Abstract: In this phenomenological study, we explored the experiences of 13 working mothers in the United States during the COVID-19 pandemic. Prior to this crisis, mothers in the workforce encountered barriers to their success. Study findings reflect that these challenges have been exacerbated during the pandemic as women experienced increased childcare and other second shift responsibilities. Results highlight participants’ strategies for navigating pandemic-related disruptions. Participants’ experiences further ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As discussed in the literature, the second shift references the inequity of labor in which the home is an additional workplace for women (Blithe, 2015, 2022; Hochschild & Machung, 2012), and, we add, mothers. Indeed, and as echoed by the mothers in our study, the COVID-19 pandemic dramatically “intensified” the second shift labor of academic mothers during the pandemic (Hermann et al, 2021, p. 19).…”
mentioning
confidence: 51%
“…As discussed in the literature, the second shift references the inequity of labor in which the home is an additional workplace for women (Blithe, 2015, 2022; Hochschild & Machung, 2012), and, we add, mothers. Indeed, and as echoed by the mothers in our study, the COVID-19 pandemic dramatically “intensified” the second shift labor of academic mothers during the pandemic (Hermann et al, 2021, p. 19).…”
mentioning
confidence: 51%
“…The disproportionate exodus of mothers from the workplace may in part be due to women receiving the lower salary in a family and/or due to socialized expectations of women [28]. However, women also were more likely to exit the workplace and assume the role of primary caregiver when they held higher level job qualifications than men [28,61].…”
Section: Employment Childcare and Household Responsibilitiesmentioning
confidence: 99%
“…Women who are mothers and employees tend to feel more guilt and stress and pick up more of the work in the home environment, often referred to as the "second shift" [61]. One COVID-19 study of parents in England explored the work balance in two-parent families and confirmed that mothers absorbed more of the housework and childcare responsibilities in most family work configurations [49], one exception being when the mother worked and the father did not.…”
Section: Employment Childcare and Household Responsibilitiesmentioning
confidence: 99%
“…Australia immediately went into complete lockdown in March of 2020 whereas many states within the US never fully locked down. For many American MotherScholars, the indecisive and inconsistent responses to the pandemic about lockdown translated to mixed messaging and confusion over how and where (home or work) to focus time and energy (Hermann et al, 2021). In contrast, data from Australia highlighted how the immediate and complete lockdown approach and extended policies supporting work from home and returning to school had positive downstream effects on parents (Herbert et al, 2020;Perper, 2020).…”
Section: Australian Versus American Academic Lifementioning
confidence: 99%